LncRNAs, RNA Therapeutics, and Emerging Technologies in Liver Pathobiology - Anwar, Abid A.; Jalan-Sakrikar, Nidhi; Huebert, Robert C. (Seminars in Liver Disease, 2024)
The field of ribonucleic acid (RNA) biology has revealed an array of noncoding RNA species, particularly long noncoding RNAs (lncRNAs), which play crucial roles in liver disease pathogenesis. This review explores the diverse functions of lncRNAs in liver pathology, including metabolic-associated steatotic liver disease, hepatocellular carcinoma, alcohol-related liver disease, and cholangiopathies such as primary sclerosing cholangitis and cholangiocarcinoma. We highlight key lncRNAs that regulate lipid metabolism, inflammation, fibrosis, and oncogenesis in the liver, demonstrating their diagnostic and therapeutic potential. Emerging RNA-based therapies, such as mRNA therapy, RNA interference, and antisense oligonucleotides, offer approaches to modulate lncRNA activity and address liver disease at a molecular level. Advances in sequencing technologies and bioinformatics pipelines are simultaneously enabling the identification and functional characterization of novel lncRNAs, driving innovation in personalized medicine. In conclusion, this review highlights the potential of lncRNAs as biomarkers and therapeutic targets in liver disease and emphasizes the need for further research into their regulatory mechanisms and clinical applications.
Keywords: lncRNA; liver disease; hepatocyte; cholangiocyte